Political essays - Locke, John, 1632-1704; Goldie, Mark (Cambridge : Cambridge University Press, 1997)
We know more about the development of John Locke's ideas than we do about almost any other philosopher's before modern times. This book brings together a comprehensive collection of the writings on politics and society that stand outside the canonical works which Locke published during his lifetime. In the aftermath of the Revolution of 1688 the three works by which he is chiefly known appeared: the Two Treatises of Government, An Essay Concerning Human Understanding, and A Letter Concerning Toleration, and the themes raised in these works had been reflected upon over many years. Mark Goldie's edition makes possible the fullest exploration of the evolution of Locke's ideas concerning the philosophical foundations of morality and sociability, the boundary of church and state, the shaping of constitutions, and the conduct of government and public policy.
Major essays. First tract on government (1660) -- Second tract on government (c. 1662) -- Essays on the law of nature (1663-4) -- An essay on toleration (1667) -- The fundamental constitutions of Carolina (1669) -- An essay on the poor law (1697) -- Minor essays. Verses on Cromwell and the Dutch War (1654) -- Verses on King Charles II Restoration (1660) -- Infallibility (1661-2) -- Verses on Queen Catherine (1662) -- On Samuel Parker (1669-70) -- Adversaria A (c. 1670?) -- Civil and ecclesiastical power (1674) -- Trade (1674) -- The particular test for priests (c. 1674) -- Philanthropy (1675) -- Catholic infallibility (1675) -- Toleration A (c. 1675) -- Obligation of penal laws (1676) -- Pleasure, pain, the passions (1676) -- Atheism (1676) -- Toleration B (1676) -- Faith and reason (1676) -- Knowledge A (1676) -- Happiness A (1676) -- Politica (1676) -- Atlantis (1676-9) -- Understanding (1677) -- Adversaria B (1677) -- Morality (c. 1677-8) -- Toleration C (1678) -- Law (1678) -- Law of nature (1678) -- Virtue A (1678) -- Happiness B (1678) -- Reputation (1678) -- Carolina (1679) -- Marriage (1679) -- Pietas (1679) -- Justitia (1679) -- Politia (1679) -- Opinion (1679) -- Love of country (1679) -- Love (1679) -- Toleration D (1679) -- Of God's justice (1680) -- Religion (1681) -- Reason, passion, superstition (1681) -- Knowledge B (1681) -- Laws (1681) -- Selecting the Grand Jury (1681) -- Virtue B (1861) -- Adversaria C (c. 1681?) -- Enthusiasm (1682) -- Ecclesia (c. 1682) -- Superstition (c. 1682) -- Tradition (c. 1682) -- The Labadists (1684) -- Thus I think (c. 1686-8?) -- Of ethic in general (c. 1686-8?) -- Pacific Christians (1688) -- On allegiance and the Revolution (1690) -- On William Sherlock (1690-1) -- Ethica A (1692) -- Ethica B (1693) -- Homo ante et post lapsum (1693) -- Voluntas (1693) -- For a general naturalisati
Title from publisher's bibliographic system (viewed on 24 Sep 2018).
Keywords: elektronické knihy; electronic books; Locke, John, -- 1632-1704.; Political science -- Early works to 1800.